Nonalcoholic Fatty Liver Disease: A Nutritional Approach - YILMAZ, YUSUF (MARY ANN LIEBERT, INC, 2012)
Nonalcoholic fatty liver disease (NAFLD) is among the most common causes of chronic liver disease in many countries, and its prevalence is increasing. NAFLD is often considered to be a hepatic component of metabolic syndrome, and studies have established that insulin resistance plays a major role in the pathogenesis of NAFLD. Treatments for NAFLD primarily target insulin resistance. Interestingly, the most common environmental cause of insulin resistance is diet. This article examines the correlations between NAFLD and diet and provides some diet recommendations based on the most current data available.
Keywords: LIFE-STYLE MODIFICATION; DE-NOVO LIPOGENESIS; INSULIN-RESISTANCE; METABOLIC SYNDROME; VITAMIN-E; HEPATIC STEATOSIS; OBESE-PATIENTS; DIETARY FRUCTOSE; LOW-CARBOHYDRATE; CONTROLLED-TRIAL